An Smc3 acetylation cycle is essential for establishment of sister chromatid cohesion. - Beckouët, F; Hu, B; Roig, M; Sutani, T; Komata, M; Uluocak, P; Katis, V; Shirahige, K; Nasmyth, K (2010)
Sister chromatid cohesion is thought to involve entrapment of sister DNAs by a tripartite ring composed of the cohesin subunits Smc1, Smc3, and Scc1. Establishment of cohesion during S phase depends on acetylation of Smc3's nucleotide-binding domain (NBD) by the Eco1 acetyl transferase. It is destroyed at the onset of anaphase due to Scc1 cleavage by separase. In yeast, Smc3 acetylation is reversed at anaphase by the Hos1 deacetylase as a consequence of Scc1 cleavage. Smc3 molecules that remain acetylated after mitosis due to Hos1 inactivation cannot generate cohesion during the subsequent S phase, implying that cohesion establishment depends on de novo acetylation during DNA replication. By inducing Smc3 deacetylation in postreplicative cells due to Hos1 overexpression, we provide evidence that Smc3 acetylation contributes to the maintenance of sister chromatid cohesion. A cycle of Smc3 NBD acetylation is therefore an essential aspect of the chromosome cycle in eukaryotic cells.